Improving Protein, Antioxidant, and Sensory Acceptance of Modified Arrowroot Composite Noodles with Black Garlic Extract for Healthy Food Innovation - Kadek Diah Puspawati, Gusti; Sekarjati, Agnes Monika Gandhes Sekarjati; Wiadnyani, Anak Agung Istri Sri; Fajarini, Luh Dian Rna; Tamalea, Rafi Renaldy (Indonesian Food Science and Technology Journal, 2026)
Composite noodles made from wheat flour with modified arrowroot starch can reduce wheat usage (30%) but require additional nutrients, have low sensory acceptance, and improve health benefits. Black garlic, a fermented form of garlic, has attracted research attention for its health benefits and unique flavor. The fortification of black garlic extract may affect product characteristics; therefore, information on the characteristics of composite wet noodles is needed to develop functional food innovations. This study aimed to investigate the effect of black garlic extract fortification on the nutrient, antioxidant, physical, and sensory properties of arrowroot composite wet noodles. The research employed a randomized block design, in which black garlic extract concentration (0%, 2%, 4%, 6%, 8%, and 10%) was fortified into composite wet noodles containing wheat flour and modified arrowroot starch that using autoclave-cooling method (70:30). The fortification of black garlic extract in 10% resulted in the best of the composite wet noodles to consume, with characteristics of 36.47% moisture content, ash content (0.43%), protein (9.95%), fat (2.4%), carbohydrate (50.75%), calories (264.40 kcal), dietary fiber (2.66%), resistant starch (1.81%), total phenolic content (0.15 mg GAE/g), total flavonoid content (0.04 mg QE/g), antioxidant activity (30.53%), the color was dark brown (L* value 38.40; a* value 7.70; b* value 54.10), water absorption (448.51%), cooking loss (12.31%), and elasticity (10.67%). The color, aroma, and taste were typical of black garlic; the texture and overall acceptance were liked. Black garlic extract improved protein, sensory acceptance, antioxidant activity, making it a healthy and potentially functional food innovation.